Influence of Classroom Management on Intermediate Level Students’ Academic Achievements in Aligarh District of Uttar Pradesh in India (International Journal of Scientific Research and Management (IJSRM), 2024)
This study investigates the impact of classroom management on student academic achievement at the intermediate level in Aligarh District, Uttar Pradesh, India, using Structural Equation Modeling-Partial Least Squares (SEM-PLS). A sample of 383 intermediate-level teachers was randomly selected, and student achievement data were obtained from final-year graduates. The study aims to assess the relationships between key classroom management factors—such as classroom rules, discipline methods, reward systems, and the teaching-learning process—and their influence on academic performance. SEM-PLS was employed to analyze the hypothesized model, evaluate the structural relationships between the variables, and validate measurement indicators. The results show a strong positive relationship between effective classroom management and student achievement. Key factors such as well-defined classroom rules, effective discipline, and reward systems were found to significantly influence student engagement and academic success. The model fit indices confirm the robustness of the proposed relationships. This research highlights the importance of structured classroom management in fostering student achievement and provides a comprehensive understanding of how classroom directives, rewards, and disciplinary methods contribute to learning outcomes. The findings suggest potential pathways for educational improvements and recommend further research to explore these dynamics across different educational settings using SEM-PLS.